Progression of carotid intima-media thickness in patients treated with lipoprotein apheresis: real-world evidence over 12 years. (14th October 2021) - Safarova, M; Gorby, L; Dutton, J; Nugent, A; Moriarty, P M
Abstract: Background: The extent of intervention effects on carotid intima-media thickness (CIMT) can predict the degree of atherosclerotic cardiovascular disease (ASCVD) risk reduction. There is limited evidence of long-term effects of lipoprotein apheresis on the CIMT progression. Purpose: We hypothesized that regular lipoprotein apheresis over the course of 10 years may slow down progression of CIMT in patients with severe hypercholesterolemia. Methods: This case series describes ten Caucasian patients (mean age 60±9 years, 70% female, 80% statin intolerant) with familial hypercholesterolemia and/or hyperlipoproteinemia(a) treated with lipoprotein apheresis at a single academic center between 2005 and 2020. The mean and maximum diastolic CIMT of the distal 1 cm of the far wall of the right and left common carotid arteries was measured by the same, trained sonographer utilizing an automated border-detection algorithm. Results: The median pre-treatment low-density lipoprotein cholesterol (LDL-C) level was 214 mg/dL (95% confidence interval, 145 to 248), lipoprotein(a), 26 mg/dL (15 to 109; 40% with lipoprotein(a) >60 mg/dL). Using the imputed trajectories, period-specific on-treatment time-weighted averages for LDL-C and lipoprotein(a) were 141 mg/dL (IQR, 89 to 152) and 24 mg/dL (IQR, 12 to 119), respectively. The baseline mean CIMT was 850±170μm and maximum CIMT was 1040±220μm across the age range of 46 to 70 years. Over a median duration of 12 years, regular treatment with lipoprotein apheresis resulted in an average reduction in the mean CIMT of −40μm (IQR, −50 to 20) and maximum CIMT −30μm (IQR, −60 to −10). Among tested lipid and lipoprotein fractions in this sample, the follow-up mean CIMT values strongly correlated only with the baseline lipoprotein(a) levels. Median CIMT progression rates were as follows: mean common carotid, −4μm/y (IQR, −9 to 1), mean common carotid, −12μm/3y (IQR, −26 to 4), maximal common carotid, −3μm/y (IQR, −8 to −1). This translated into 70% (7/10) of cases demonstrating composite mean CIMT below their expected chronologic age, gender and race-stratified vascular age. There was a strong direct correlation between the mean CIMT value at the end of the treatment period and the age of treatment initiation. In this cohort of primary and secondary prevention of patients with severe hypercholesterolemia, the overall rate of ASCVD was 37.5 per 1000 person-years while on lipoprotein apheresis. Conclusions: Our observation performed in the clinical setting, demonstrated a real-world effectiveness of lipoprotein apheresis. This analysis supports implementation of aggressive lipid-modifying strategies across all ages. Surveillance with CIMT allows for continued monitoring of atherosclerosis progression and increases compliance with the lipid-modifying therapies in the high-risk patients with poor statin tolerance in the clinical setting. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): KUMC